Observed classroom quality in first grade: associations with teacher, classroom, and school characteristics - Joana Cadima (2013)
The observation and assessment of quality of teacher-child interactions in elementary school settings are increasingly recognized as important; however, research is still very limited in European countries. In this study, we examined the quality of the interactions between teacher and children in first-grade classrooms in Portugal and the extent to which structural features at teacher-, classroom-, and school-level explained variation in this quality. One hundred fifteen classrooms participated in the study. Classrooms were observed through a standardized rating scale concerning emotional, organizational, and instructional support. Results indicated that the levels of emotional and organizational support in most classrooms were of moderate quality, but the levels of instructional support were low, suggesting that most observed activities did not encourage students' higher-order thinking skills. An examination of the associations between teacher and classroom characteristics and the quality of teacher-child interactions indicated a small effect for teacher education. Teachers with an advanced degree were more likely to be more emotionally sensitive and to have better instructional interactions in the classroom. For school-level characteristics, findings showed that the classrooms in private and smaller schools were likely to provide higher levels of emotional, organizational, and instructional quality. The results suggest that focusing on the interactions between teacher and children can provide valuable information to enhance classroom quality. (c) 2013 Instituto Superior de Psicologia Aplicada, Lisboa, Portugal and Springer Science+Business Media Dordrecht.